The influence of early diet quality on the mental health of college students: the mediation effects of height and qi-deficiency - Wang, Xinzhu; He, Xinyu; Fu, Kaixian; Zhang, Yuxia (Frontiers in Public Health, 2024)
Background: In China, the prevalence of mental health issues among college students is a significant concern in society. This study aims to investigate the impact of early dietary quality on the psychological well-being of college students and elucidate the underlying mechanisms through which these effects occur, specifically focusing on height and qi-deficiency as mediators according to Chinese traditional medicine (CTM).Methods: A total of 655 college students were surveyed in October 2023 using paper-pencil-based questionnaires at four second-tier universities in Sichuan Province. The assessment included mental health, height, and qi-deficiency. Pearson's correlation and linear regression analyses were employed to examine the mediation model and test the hypotheses.Results: The college students exhibited acceptable levels of early diet quality (M=3.72) and mental health (M=3.63), while also presenting mild qi-deficiency symptoms (M=2.25). Their average height was measured at 164.61 cm. Early diet quality demonstrated significant associations with mental health (r=0.38, p<0.01), height (r=0.32, p<0.01), and qi-deficiency (r=-0.32, p<0.01). Mental health displayed correlations with height (r=0.32, p<0.01) and qi-deficiency (r=-0.49, p<0.01). The results of linear regression analyses revealed significant associations between early diet quality and mental health (β=0.31, p<0.01), height (β=0.21, p<0.01), as well as qi-deficiency (β=-0.26, p<0.01). Furthermore, when early diet quality was included in the regression model, both height (β=0.21, p<0.01) and qi-deficiency (β=-0.35, p<0.01) emerged as significant mediators in the relationship with mental health.Conclusions: The mediation model and hypotheses were strongly supported, demonstrating that early diet quality exerted an influence on the mental health of college students through two distinct pathways: height and qi-deficiency. Moreover, the mediating effect of qi-deficiency was found to be more pronounced than that of height in the relationship between early diet quality and mental health among college students.